Self-Talk Strategy: A Qualitative Investigation in Building English Speaking Skill - Usuluddin; Dwimaulani, Astrid; Mawarni, Iga Anggi; Marzuki, M. Junaidi (PROJECT (Professional Journal of English Education), 2026)
This study investigates the types of self-talk and students' perceptions of the impact of using self-talk in building their English-speaking skills. By using a qualitative descriptive approach, data were collected through questionnaires, semi-structured interviews, and observations with six second-semester students of the English language education program at Universitas Hamzanwadi. The findings reveal that students used two types of self-talk strategies to build their English-speaking skills, which are instructional self-talk and motivational self-talk. Students viewed self-talk as an effective strategy to support technical preparation for speaking, reduce anxiety, and increase self-confidence. The benefits of using self-talk include reduced anxiety and nervousness, increased confidence, motivation, fluency, and skills, as well as creating space for self-practice. Thus, it can be concluded that self-talk is proven to be a solution for regulating affective and cognitive aspects in order to build English speaking skills.